Characterization of a dielectric barrier discharge in contact with liquid and producing a plasma activated water. (21st December 2016) - Neretti, G; Taglioli, M; Colonna, G; Borghi, C A
Abstract: In this work a low-temperature plasma source for the generation of plasma activated water (PAW) is developed and characterized. The plasma reactor was operated by means of an atmospheric-pressure air dielectric barrier discharge (DBD). The plasma generated is in contact with the water surface and is able to chemically activate the liquid medium. Electrodes were supplied by both sinusoidal and nanosecond-pulsed voltage waveforms. Treatment times were varied from 2 to 12 min to increase the energy dose released to the water by the DBD plasma. The physics of the discharge was studied by means of electrical, spectroscopic and imaging diagnostics. The interaction between the plasma and the liquid was investigated as well. Temperature and composition of the treated water were detected. Images of the discharges showed a filamentary behaviour in the sinusoidal case and a more homogeneous behaviour in the nanosecond-pulsed one. The images and the electrical measurements allowed to evaluate an average electron number density of about 4  ×  10 19 and 6  ×  10 17 m −3 for the sinusoidal and nanosecond-pulsed discharges respectively. Electron temperatures in the range of 2.1÷2.6 eV were measured by using spectroscopic diagnostics. Rotational temperatures in the range of 318–475 K were estimated by fitting synthetic spectra with the measured ones. Water temperature and pH level did not change significantly after the exposure to the DBD plasma. The production of ozone and hydrogen peroxide within the water was enhanced by increasing the plasma treatment time and the energy dose. Numerical simulations of the nanosecond-pulsed discharge were performed by using a self-consistent coupling of state-to-state kinetics of the air mixture with the Boltzmann equation of free electron kinetics. Temporal evolution of the electron energy distribution function shows departure from the Maxwellian distribution especially during the afterglow phase of the discharge. When limited deviations from Maxwellian distribution were observed, calculated electron temperature is in good agreement with the one measured by means of spectroscopic diagnostics. Computed temporal evolution of the energy delivered to the discharge is comparable with the one obtained from electrical measurements. The electrical discharges supplied by both voltage waveforms produce plasma activated water with negligible thermal effects and pH variations.